Halogen bond tunability II: the varying roles of electrostatic and dispersion contributions to attraction in halogen bonds - Riley, Kevin E; Murray, Jane S; Fanfrlík, Jindřich; Rezáč, Jan; Solá, Ricardo J; Concha, Monica C; Ramos, Felix M; Politzer, Peter (Journal of molecular modeling, 2013)
In a previous study we investigated the effects of aromatic fluorine substitution on the strengths of the halogen bonds in halobenzene…acetone complexes (halo = chloro, bromo, and iodo). In this work, we have examined the origins of these halogen bonds (excluding the iodo systems), more specifically, the relative contributions of electrostatic and dispersion forces in these interactions and how these contributions change when halogen σ-holes are modified. These studies have been carried out using density functional symmetry adapted perturbation theory (DFT-SAPT) and through analyses of intermolecular correlation energies and molecular electrostatic potentials. It is found that electrostatic and dispersion contributions to attraction in halogen bonds vary from complex to complex, but are generally quite similar in magnitude. Not surprisingly, increasing the size and positive nature of a halogen's σ-hole dramatically enhances the strength of the electrostatic component of the halogen bonding interaction. Not so obviously, halogens with larger, more positive σ-holes tend to exhibit weaker dispersion interactions, which is attributable to the lower local polarizabilities of the larger σ-holes.